The Effectiveness of the Flash Card-Assisted Make-A-Match Model on the Interest and Learning Outcomes of Fourth Grade Mathematics Students - Tando', Wanda Lestari; Syam, Nur; Saputra, Andi Muhammad Akbar (EduLine: Journal of Education and Learning Innovation, 2025)
This study aimed to determine the effectiveness of the Make a Match cooperative learning model, using Flash Cards, in improving fourth-grade students' interest and learning outcomes in mathematics. Data were obtained through a quantitative approach with a one-group pretest-posttest experimental design involving 29 fourth-grade students at Kapasa Public Elementary School in Makassar City. The research instruments consisted of a learning outcome test to measure cognitive aspects and a questionnaire to assess student learning interest. Data analysis was conducted using a paired sample t-test to compare scores before and after the treatment. The analysis results showed a significant difference between the pretest and posttest scores for both interest and learning outcomes, with a significance value (Sig. 2-tailed) of 0.000 < 0.05. This difference confirms that the applied learning model positively influences student engagement and learning outcomes. The main findings of this study indicate that the implementation of the Make a Match model, using Flash Cards, is effective in creating a more active and enjoyable learning environment, and significantly improving fourth-grade students' interest and learning outcomes in mathematics.